Determinantes da taxa de ocupação hoteleira no Brasil - Sousa, José Marcelino de Oliveira (2014)
The objective of this work is to construct a function of demand for hotel services to Brazil, in order to offer the hotel industry a proper diagnosis of the main determinants of occupancy. This process will be conducted based on information extracted from the Hotel Operators Forum Brazil - FOHB, which presents observations on the rate of occupancy, RevPAR, daily price, location, seasonality and flow individuals to ten Brazilian capitals, which are São Paulo, Rio de Janeiro, Vitória, Belo Horizonte, Fortaleza, Salvador, Brasília, Curitiba, Porto Alegreand Manaus. The data are presented on a monthly basis and corresponds to the period between January 2009 and December 2012. The methodology used is based on the technique of panel data, in its versions for fixed effect, random effect and dynamic model . The results highlight the prejudicial effect of the daily rate, the seasonal component and the flow of individuals on the occupation, while the dummy location and RevPAR positively impacted. These facts indicate that the hotel service is a very common type, which exhibit negative changes in consumption during the low season and positive the higher the quality of service fluctuations.